Local beliefs and religious practices of Parmalim in North Sumatra - Marahuddin, Marahuddin; Dalimunthe, Alwinsyah; Asadi, Akram (UIN Sunan Gunung Djati Bandung, 2025)
Indonesian society is renowned for its rich diversity of religious traditions, including local beliefs that persist to this day. One such tradition is the Parmalim Religion, which originates from the Batak tribe in North Sumatra. This religion, also known as Ugamo Malim, is a belief system that regulates the spiritual relationship between humans and the spirit world, with Debata Mulajadi Na Bolon as God who created the universe. Religious practices in the Parmalim Religion involve various rituals and ceremonies that reflect the depth of humans' relationship with God and the natural environment, such as birth, marriage, and death rituals, as well as annual ceremonies related to the harvest season and the Batak New Year. This religion encompasses moral values such as solidarity, justice, and togetherness, which guide the daily lives of its adherents. This research uses a literature-based qualitative approach to examine Parmalim's religious practices, utilizing William James' theory of religious experience and Emile Durkheim's theory of religious practice. This study aims to provide a deeper understanding of how the Parmalim Religion maintains the spiritual and cultural identity of the Batak people and its contribution to the diversity of religious practices in Indonesia. Through an analysis of written sources, it is hoped that this research will enrich our understanding of local beliefs and their preservation amidst current developments.